Chronic Kidney Disease in Jigawa State, Nigeria; A silently Emerging Epidemic? - Ibrahim, Abdullahi Haruna; Aikawa, Hussaini Muhammad; Ladan, Muhammad Awwal; Sani, Sa’adatu Muhammad; Iliya, Rahmatu Shamsiyyah; Mohammed, Auwalu; Ibrahim, Usman (REAL in Nursing Journal, 2023)
Purpose: The study was conducted to examine the trend of chronic kidney disease (CKD) in as seen at Rasheed Shekoni Teaching Hospital (RSTH), Dutse, a state referral centre for CKD cases in Jigawa state over a six-year period from January 2015 to December 2020. Methods: Retrospective research design was used where all the 621 cases seen in the facility over the study period were retrieved and reviewed. Ethical clearance was obtained from the Research and Ethics Committee of RSTH. Data was analysed using frequency tables, charts and multiple regression analysis. Results: The result revealed the mean age of the cases as 39±1 and 62% were males. While the CKD burden between 2016 (51) and 2016 (47) were relatively lower than the later years, a marked increase in the number of CKD cases was witnessed in the facility in 2017 (147) and the curve plateaued at such high prevalence through 2018 (155) and 2019 (151) until 2020 where a drastic drop (70) was witnessed were only 11.2% of the cases were seen. Conclusion: The findings further revealed having chronic glomerulonephritis, comorbidities of hypertension and chronic glomerulonephritis and, hypertension and diabetes, being 60 years & above and being male (p<0.05) as the predictors of having CKD among the patients seen at the facility. It was concluded that, there is a growing trend in the burden of CKD in the state and there is need for further investigations to determine the factors behind it in order to proffer solution to the problem.